Digital Marketing, Social media, and Public Trust: A Mediation Model of Prospective Cadet Enrollment Intention in Maritime Higher Education - Retno Sawitri Wulandari; Isra Ferdinand; Natanael Suranta; B. B. Harianto; Retno Sawitri Wulandari; Isra Ferdinand; Natanael Suranta; B. B. Harianto (Universitas Negeri Malang, 2026)
The rapid expansion of digital marketing and social media has transformed student recruitment strategies in higher education, particularly in competitive and specialized institutions. However, the mechanisms through which digital strategies translate into actual enrollment intention remain theoretically and empirically contested. This study examines how Digital Marketing and Social media influence Prospective Cadet Interest through the mediating role of Public Trust in a maritime higher education institution. Using a quantitative explanatory design, data were collected from 97 respondents drawn proportionally from a population of 2,836 applicants (2020–2023). The model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships among constructs. Results indicate that Digital Marketing and social media significantly enhance Public Trust and directly influence Prospective Cadet Interest. Public Trust also exerts a significant positive effect on enrollment intention and partially mediates the relation between digital strategies and interest. Measurement and structural models satisfied reliability and validity criteria, confirming the robustness of the proposed mediation framework. These findings highlight the strategic importance of trust-based digital communication, demonstrating that credible signaling and engagement quality are essential for converting digital visibility into enrollment growth in specialized higher education contexts.